PRECIOUS: PREvention of Complications to Improve OUtcome in elderly patients with acute Stroke: rationale and design of a randomised, open, phase III, clinical trial with blinded outcome assessment - Reinink, Hendrik; de Jonge, Jeroen C.; Bath, Philip M.; van de Beek, Diederik; Berge, Eivind; Borregaard, Saskia; Ciccone, Alfonso; Csiba, Laszlo; Demotes, Jacques; Dippel, Diederik W.; Korv, Janika; Kurkowska-Jastrzebska, Iwona; et al. (Sage, 2018)
Background: Elderly patients are at high risk of complications after stroke, such as infections and fever. The occurrence of these complications has been associated with an increased risk of death or dependency. Hypothesis: Prevention of aspiration, infections, or fever with metoclopramide, ceftriaxone, paracetamol, or any combination of these in the first four days after stroke onset will improve functional outcome at 90 days in elderly patients with acute stroke. Design: International, 3 × 2-factorial, randomised-controlled, open-label clinical trial with blinded outcome assessment (PROBE) in 3800 patients aged 66 years or older with acute ischaemic stroke or intracerebral haemorrhage and an NIHSS score ≥ 6. Patients will be randomly allocated to any combination of oral, rectal, or intravenous metoclopramide (10 mg thrice daily); intravenous ceftriaxone (2000 mg once daily); oral, rectal, or intravenous paracetamol (1000 mg four times daily); or usual care, started within 24 h after symptom onset and continued for four days or until complete recovery or discharge from hospital, if earlier. Outcome: The primary outcome measure is the score on the modified Rankin Scale at 90 days (± 14 days), as analysed with multiple regression. Summary: This trial will provide evidence for a simple, safe and generally available treatment strategy that may reduce the burden of death or disability in patients with stroke at very low costs. Planning: First patient included in May 2016; final follow-up of the last patient by April 2020